1980
DOI: 10.1021/np50010a001
|View full text |Cite
|
Sign up to set email alerts
|

A Brief Survey of Taxus Alkaloids and Other Taxane Derivatives

Abstract: Alkaloids of the Taxaceae are briefly surveyed. Compounds containing the taxane nucleus are reviewed, including discussions of their isolation, nomenclature, and nmr, ms and X-ray analyses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
5

Year Published

1983
1983
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(36 citation statements)
references
References 17 publications
0
31
0
5
Order By: Relevance
“…± Since the 1980s, paclitaxel (1) [1], a well-known antitumor diterpenoid [2], has been adopted in the therapy of some cancer types [3]. Owing to its low solubility, it is administered as a castor oil (Cremophor )/EtOH solution.…”
mentioning
confidence: 99%
“…± Since the 1980s, paclitaxel (1) [1], a well-known antitumor diterpenoid [2], has been adopted in the therapy of some cancer types [3]. Owing to its low solubility, it is administered as a castor oil (Cremophor )/EtOH solution.…”
mentioning
confidence: 99%
“…In addition to the names taxine and taxol, names such as taxicin, taxacin, taxagifi ne, taxinin, taxusin, taxanine, taxicatin, taxinol, and taxininol have been applied to various isolations (Miller 1980;Khan and Parveen 1987). In addition to the names taxine and taxol, names such as taxicin, taxacin, taxagifi ne, taxinin, taxusin, taxanine, taxicatin, taxinol, and taxininol have been applied to various isolations (Miller 1980;Khan and Parveen 1987).…”
Section: Taxaceae Agraymentioning
confidence: 99%
“…Appendino et al, (1992) have identified two constituents taxine A (30%) and taxine B (2%) from an amorphous basic fraction known as taxine from the needles of T. wallichiana. Further, an impressive array of taxanes and other analogues, 10-deacetyl-baccatin III, 10-deacetyl-taxol, cephalomannine, 10-deacetyl-cephalomannine, 19-hydroxy-baccatin III were also identified and these are being used as intermediates for the semi-synthesis of Taxol (Appendino et al, 1993;Miller 1980;Mclaughlin et al, 1981). Presence of biflavonesamentoflavone, sciadopitysin, ginkgetin and scquoiaflavone were identified from the leaves of T. wallichiana.…”
Section: Abies Spectabilismentioning
confidence: 99%